Usability of car stereo - Razza, Bruno Montanari; Paschoarelli, Luis Carlos [UNESP] (IOS Press, 2012)
Automotive sound systems vary widely in terms of functions and way of use between different brands and models what can bring difficulties and lack of consistency to the user. This study aimed to analyze the usability of car stereo commonly found in the market. Four products were analyzed by task analysis and after use reports and the results indicate serious usability issues with respect to the form of operation, organization, clarity and quality of information, visibility and readability, among others.